Current status and strategies for conservation of Hariana cattle - KUMAR, Manoj; DAHIYA, S P; RATWAN, POONAM (The Indian Journal of Animal Sciences, 2019)
In the present review, an attempt was made to explore Hariana cattle, an important dual purpose breed for its genetic improvement, conservation and further research. The production, reproduction and functional traits of Hariana cattle are reviewed. Average lactation milk yield, wet average, lactation milk yield per day of calving interval, average lactation length, dry period, age at first calving, service period and calving interval varied from 721.18±13.3–2215.07±24.58 kg, 2.45±0.05–4.97±0.09 kg, 1.10±0.03–2.38±0.13 kg, 252.30±2.95–336.00±4.3 days, 133.03±10.12–336±4.3 days, 1037.93±5.95–1762±12 days, 154.0±9.30–302.70±6.50 days and 421–630.8±9.0 days, respectively. The heritability estimates for the above mentioned traits varied from 0.11±0.08–0.50±0.16, 0.16±0.09– 0.27±0.14, 0.33±0.14–0.39±0.22, 0.09±0.08–0.80, 0.09±0.08–0.32±0.32, 0.18±0.13–0.67±0.15, 0.05±0.19– 0.24±0.16 and 0.02±0.06–0.41±0.14, respectively. Major factors for the decline of Hariana cattle population were marketing problem, low milk yield, less milk fat percentage as compared to buffalo milk, and mechanization of agriculture. Hariana cattle is famous for its remarkable power of endurance for hot climate of tropics, resistance to tropical diseases and has low maintenance cost besides providing A2 milk. Hariana cattle can be conserved by creating public awareness about good qualities of the breed. Government should provide incentives to the farmers in terms of semen supply and treatment of the animals. There is a need of raising progeny tested bulls and development of pastures at community as well as panchayat land. Government or NGOs should participate actively and there is a need to start registered societies for propagation and conservation of Hariana cattle.